ОСОБЕННОСТИ КОМПЕТЕНТНОЙ ПОДГОТОВКИ СПЕЦИАЛИСТОВ 1С (International Journal of Innovative Technologies in Economy, 2018)
Qualitative training of specialists is a priority direction of educational institutions. Information is one of the subjects of work of the company’s specialists, without having a clear structured information base, which specialists can not take the right management decision, which jeopardizes the company’s activities.